First malaria infections in a cohort of infants in Benin: biological, environmental and genetic determinants. Description of the study site, population methods and preliminary results. Issue 2 (8th March 2012) - Le Port, Agnès; Cottrell, Gilles; Martin-Prevel, Yves; Migot-Nabias, Florence; Cot, Michel; Garcia, André
Abstract : Objectives: Malaria infection of the placenta during pregnancy was found to be associated with infant susceptibility to malaria. Other factors such as the intensity of malaria transmission and the nutritional status of the child might also play a role, which has not been adequately taken into account in previous studies. The aim of this study was to assess precisely the parts played by environmental, nutritional and biological determinants in first malaria infections, with a special interest in the role of placental infection. The objective of this paper is not to present final results but to outline the rationale of the study, to describe the methods used and to report baseline data. Design: A cohort of infants followed with a parasitological (symptomatic and asymptomatic parasitaemia) and nutritional follow-up from birth to 18 months. Ecological, entomological and behavioural data were collected along the duration of the study. Setting: A rural area in Benin with two seasonal peaks in malaria transmission. Participants: 656 infants of women willing to participate in the study, giving birth in one of the three maternity clinics and living in one of the nine villages of the study area. Primary Outcome Measures: The time and frequency of first malaria parasitaemias in infants, according to Plasmodium falciparum infection of the placenta. Results: 11% of mothers had a malaria-infected placenta at delivery. Mosquito catches made every 6 weeks in the area showed an average annual P falciparum entomological inoculation rate of 15.5, with important time and space variations depending on villages. Similarly, the distribution of rainfalls, maximal during the two rainy seasons, was heterogeneous over the area. Conclusions: Considering the multidisciplinary approach of all factors potentially influencing the malaria status of newborn babies, this study should bring evidence on the implication of placental malaria in the occurrence of first malaria infections in infants.